Comparison of Blood Lead Level between Conventional Cigarette Smokers and Electronic Smokers in a Sample of Iraqi Adult Males - Hussein, Huda Jabbar; AlـWasiti, Prof. Estabraq A.R.AlـWasiti (Academic Journal of Clinicians, 2025)
Background Lead exposure remains a critical public health issue due to its multi-systemic toxicity, even at low levels. Smoking is a significant source of lead exposure, with tobacco and e-cigarettes being potential contributors. Despite the perception of e-cigarettes as a safer alternative, their impact on blood lead levels (BLL) is not well-documented. Objective: To compare blood lead levels among conventional cigarette smokers, e-cigarette smokers, and non-smokers in a sample of Iraqi adult males. Patients and Methods This case-control study was conducted from January to December 2024 at Al-Nahrain University and Al-Imamain Kadhimain Medical City. A total of 150 adult males were categorized into three groups: conventional cigarette smokers (n=50), e-cigarette smokers (n=50), and non-smokers (n=50). Participants were assessed for demographic variables, smoking history, and blood lead levels using atomic absorption spectrophotometry. Statistical analysis was performed using SPSS v26, with significance set at p<0.05. Results Conventional cigarette smokers exhibited the highest mean blood lead level (23.78 ± 2.19 µg/dL), followed by e-cigarette smokers (21 ± 2.5 µg/dL) and non-smokers (6.6 ± 3.1 µg/dL). The differences among the groups were statistically significant (p=0.00001). Smoking intensity correlated strongly with blood lead level in both conventional (r=0.92) and e-cigarette smokers (r=0.90). No significant association was found between BLL and demographic factors such as age or BMI. Conclusion: Both conventional and e-cigarette smoking are associated with significantly elevated blood lead levels compared to non-smoking. While e-cigarettes exhibit lower lead levels than conventional cigarettes, they are not risk-free. These findings underscore the need for stricter regulations on smoking products and public health interventions to reduce lead exposure. Keywords: Blood Lead Level, Smoking , Conventional Cigarette, Electronic, Iraqi Adult Males